The notion of nature in modern music theory and history as seen hy Carl Dahlhaus and Karol Berger - Jarzębska, Alicja (Interdisciplinary Studies in Musicology, 2018)
Modern music theory, ignoring the problems connected with the subject’s auditive experience but referring to the objective laws of nature, was criticised by Carl Dahlhaus, although he accepted - to a certain extent - the hypothesis of historical determinism. Dahlhaus links this turning point in the history of reflection on music with the transition from the ‘ontological contemplation’ of the Tonsystem to the ‘aesthetic contemplation’ of the Tonkunstwerk, the fundamental characteristic of which is the idea of ‘wholeness’ (die Idee der Ganzheit). The new conception of the discourse on the theory and history of modern music proposed by Karol Berger in his book A Theory of Art (2000) bears testimony to crucial changes in the contemporary humanities linked to the so-called ‘cognitive revolution’. According to Berger, the fundamental characteristic distinguishing modern art from premodern art is its autonomy. Berger distances himself from the modern tradition of theoretic- aesthetic discourse treating the work of art, including the work of music, as an axiologically neutral entity independent of ‘human nature’, that is, of the functioning of our memory, imagination and cognitive mechanisms, and also not having a specific social function. At the centre of Berger’s theoretical interests is aesthetics, as broadly understood, coupled with ethics and history, poetics and hermeneutics. He is not interested - like Dahlhaus - in considering ‘what art is’ or ‘what music is’ , but poses the question: ‘What should the function of art be, if art is to have a value for us ?’